Expanding medicaid coverage for early treatment of hiv-positive persons and the implications for poverty reduction\ Gabriel Tourek - Tourek, Gabriel (2010)
Since the outbreak of HIV/AIDS in the United States in the early 1980s, Congress has extended in-kind treatment benefits to HIV-positive persons under Medicaid and, more recently, Medicare AIDS Drug Assistance Programs (ADAPs). People who do become infected and who cannot afford care eventually receive antiretroviral (ARV) therapy funded by Federal and state public health insurance; however, Medicaid imposes an eligibility requirement mandating a demonstration of "severely disability" as a condition for receiving AIDS treatment. Medicaid (and Medicare) eligibility requirements restrict benefits to HIVpositive individuals who are completely incapacitated while access is deferred for those struggling in the interim before severe disability. De facto, HIV-positive Medicaid recipients - low-income sufferers and the majority of infected persons of color -experience shorter life expectancies and lower qualities of life than their privately-insured counterparts.